2020
DOI: 10.3390/ijerph17103361
|View full text |Cite
|
Sign up to set email alerts
|

Examining Shopping Patterns, Use of Food-Related Resources, and Proposed Solutions to Improve Healthy Food Access Among Food Insecure and Food Secure Eastern North Carolina Residents

Abstract: In the Southern United States (U.S.), food insecurity rates are higher in rural (20.8%) versus urban communities (15%). Food insecurity can exacerbate diet-related disease. Thus, the purpose of this study was to examine differences in the use of food-related community resources and potential solutions proposed among food insecure versus food secure residents. A community survey (n = 370) was conducted in rural eastern North Carolina, with questions pertaining to food security status and food-related resources.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…To bridge the gap in food access, our study participants reported bartering for food, gardening, hunting/fishing, visiting food pantries, and shopping at dollar stores. Our participants generally had a negative opinion of home gardening, which supports a recent study reporting that rural food insecure persons were less likely to have a garden than food secure persons [ 14 ]. Other recent studies suggest gardening is perceived positively by white rural residents [ 12 , 39 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…To bridge the gap in food access, our study participants reported bartering for food, gardening, hunting/fishing, visiting food pantries, and shopping at dollar stores. Our participants generally had a negative opinion of home gardening, which supports a recent study reporting that rural food insecure persons were less likely to have a garden than food secure persons [ 14 ]. Other recent studies suggest gardening is perceived positively by white rural residents [ 12 , 39 ].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, our findings suggest that living in rural locations, being poor and a minority may contribute to food insecurity. Previous research among rural food insecure persons has largely focused on White audiences, [ 12 , 29 , 37 ] and very few have included the perceptions of rural, low-income Black audiences, which experience a higher prevalence of food insecurity [ 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings provide evidence of the potential impact of such assistance on food access in an Appalachian community. Southern rural community members, regardless of food security status, have been found to use community resources such as cooking classes, farmers’ markets, and community gardens equally [ 27 , 28 ]. Furthermore, SNAP benefits provide a rapid, effective economic stimulus, generating USD $1.70 for each dollar spent [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community gardens and farmers markets have been shown to help improve access to fresh produce, integrating nutritious food access into the community's built environment while encouraging participation in aid programs like SNAP [ 78 , 95 ]. Given the reduced cardiovascular risk associated with increased fruit and vegetable intake, increasing fruit and vegetable access via these community initiatives would improve both food security status and cardiovascular health [ 96 ]. Alternatives to simply opening more grocery stores in low access areas, such as sugary drink taxes and local nutrition education programs, have also been shown to improve dietary quality among the food insecure and improve their cardiovascular outcomes [ 95 , 97 , 98 ].…”
Section: Knowledge Gaps Opportunities For Interventions and Future Directionsmentioning
confidence: 99%